Chilean pepper: Spoilage fungi and mycotoxins contamination risk in Capsicum products - Costa, Jéssica (2019)
Capsicum products, such as chilli powder, paprika, sauces, and spice mix, have highly been consumed worldwide.In Chile, berry fruits of Capsicum annuum L. cv. “Cacho de Cabra” are used for the manufacture of a traditional pepper powder known as Merkén. Two alert notifications regarding the presence of Ochratoxin A in Merkén have been reported by the Chilean Ministry of Health. These alerts have triggered concern mainly due to the food safety of Capsicum derivative products and the health risks to which the Chilean population consumers of Merkén may be subjected. In this context, the main aim of this work was to review the critical points of mycotoxin contamination in the Capsicum production chain used for Merkén manufacture in Chile; outlining the possible causal agents of mycotoxin contamination in Merkén production chain. Current national and international legislation on mycotoxin contamination in pepper and its derivative are here discussed. Moreover, preventive and corrective measures adopted by the Chilean regulators’ agencies to control mycotoxin in this spice are also discussed.